Penerapan Teknik Glasir dan Lukis untuk Pewarnaan Keramik Tableware - Sanusi, Angeline; Pemayun, Tjokorda; Utami, Purnami (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2026)
This study explores the application of glazing and underglaze painting techniques in the creation of ceramic tableware inspired by the aesthetic qualities of plant forms. The research adopts a practice-based artistic approach consisting of observation, exploration, and material embodiment in ceramic media. The artworks produced include a series of functional tableware items, specifically three cups and three bowls, created using wheel-throwing and handbuilding techniques. Surface decoration was developed through carving and coloring processes that combine underglaze painting and glaze finishing to produce varied visual effects. The findings demonstrate that the integration of multiple coloring techniques enhances both the aesthetic quality and functional value of ceramic tableware. This study contributes to the development of creative strategies in ceramic art practice, particularly in the exploration of decorative surface treatments.